The ultrasonic nonlinearity parameter for biological media - DUNN, F.; LAW, W. K.; FRIZZELL, L. A. (Archives of Acoustics, 1984)
The nonlinearity parameter B/A of several soft tissues was measured using two independent methods. The B/A values of most soft tissues were found to be between 7 and 8, with the exception of fat which has a B/A value close to 11. It is proposed that structural hierarchy contributes to the BM values of tissues.